The experience of people with multiple sclerosis who receive occupational performance coaching - Niloufar Malakouti; Dorothy Kessler; Marcia Finlayson; Samantha Stephens (PEC Innovation, 2025)
Objective: To explore how Occupational Performance Coaching (OPC) influences self-management in the daily lives of people with Multiple Sclerosis (PwMS). Methods: A qualitative study involving 10 PwMS who underwent 6 sessions of telephone OPC over ten weeks. Interpretive description was used as the methodological approach. Participants were interviewed pre- and post-intervention, with thematic analysis performed on transcripts. Results: Pre-intervention themes included resisting MS, living with MS, ongoing challenges, and strategies. Post-intervention, the theme of resisting MS dissipated, with emergent sub-themes of planning ahead, being consistent, and talking about the plan. Participants reported reduced resistance towards their condition, a shift in their focus from problems towards solutions, and an enhancement of existing strategies and/or development of new strategies used to overcome ongoing challenges in living with MS. Conclusion: OPC may facilitate a shift in focus towards solutions and enhance self-management strategies in PwMS. Innovation: This study highlights OPC as a promising and innovative approach for addressing the self-management needs of individuals with MS, emphasizing its potential to enhance meaningful participation by fostering effective coping strategies and proactive attitudes.